2020
DOI: 10.1016/j.cub.2020.02.091
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Cortical Integration of Sensory and Affective Pain Pathways

Abstract: Highlights d Anterior cingulate cortex (ACC) receives inputs from the somatosensory cortex (S1) d Activation of the S1 inputs increases the nociceptive response in the ACC d This cortico-cortical projection regulates pain-aversive behaviors d Chronic pain enhances the connection between the S1 and the ACC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 63 publications
5
102
0
Order By: Relevance
“…The rACC-injected NMDA receptor antagonist significantly inhibited F-CPA in rats; however, it did not reduce acute formalin-induced nociceptive behaviors ( Ren et al, 2006 ). The engagement of the rACC circuitry has been shown to be associated with the modulation of the affective component without altering pain intensity ( Singh et al, 2020 ). Interestingly, our present study also demonstrated that chemogenetic inhibition of glutamatergic neurons in the rACC-thalamus circuitry only reduced anxiety disorders without changing the rats’ pain thresholds induced by CFA.…”
Section: Discussionmentioning
confidence: 99%
“…The rACC-injected NMDA receptor antagonist significantly inhibited F-CPA in rats; however, it did not reduce acute formalin-induced nociceptive behaviors ( Ren et al, 2006 ). The engagement of the rACC circuitry has been shown to be associated with the modulation of the affective component without altering pain intensity ( Singh et al, 2020 ). Interestingly, our present study also demonstrated that chemogenetic inhibition of glutamatergic neurons in the rACC-thalamus circuitry only reduced anxiety disorders without changing the rats’ pain thresholds induced by CFA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 26 28 ] These findings have been replicated in other model systems, including rabbits and monkeys, where increases in extracellular activity in the ACC have been observed to occur in response to stimulations in freely moving animals and humans [ 29 32 ]. Furthermore, studies have shown that ACC neurons undergo synaptic plasticity in chronic pain conditions [ 7 , 25 , 33 ]. Thus, there is a possibility that neuronal responses to noxious stimuli in the ACC may show distinct patterns in the chronic pain state.…”
Section: Introductionmentioning
confidence: 99%
“…In ACC the increased activity is most likely because, the activation is limited when using a stimulus less than ten times the motor threshold (Chang & Shyu, 2001; Shyu et al., 2008; Yang et al., 2006). In addition, several studies confirm this finding as ACC has increased activation when using noxious stimuli compared to non‐noxious stimuli (Singh et al., 2020; Zhang et al., 2018). Based on previous research, it was expected that the peak activity in ACC would be smaller (Chang & Shyu, 2001) and slower (Kuo & Yen, 2005; Wang et al., 2008; Xiao et al., 2019) than that in SI when using noxious stimuli.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies using complete Freund's adjuvant (CFA) showed modulated activity in SI to non‐noxious stimuli (Tan et al., 2019) and noxious stimuli (Singh et al., 2020) and in ACC to noxious stimuli (Singh et al., 2020; Zhang et al., 2018). The processing in ACC of electrical stimuli in Onishi et al.…”
Section: Introductionmentioning
confidence: 99%